Acute Stroke After Carotid Endarterectomy: Time for a Paradigm Shift? Multicenter Experience With Emergent Carotid Artery Stenting With or Without Intracranial Tandem Occlusion Thrombectomy. Issue 4 (23rd January 2015) - Spiotta, Alejandro M.; Vargas, Jan; Zuckerman, Scott; Mokin, Maxim; Ahmed, Azam; Mocco, J.; Turner, Raymond D.; Turk, Aquilla S.; Chaudry, M. Imran; Myers, Phil
Abstract: BACKGROUND: Stroke in the immediate postoperative period after carotid endarterectomy is a rare complication. Many centers have begun incorporating angiography before surgical re-exploration, which has the advantage of confirming carotid occlusion and treating tandem intracranial lesions if present. OBJECTIVE: To determine the safety and efficacy of this strategy. METHODS: A retrospective review was performed of all patients undergoing acute stenting of the carotid artery after carotid endarterectomy from November 2009 to June 2013 at 4 centers. Charts and angiographic images were reviewed. Eleven cases of carotid thrombosis within 72 hours of carotid endarterectomy and subsequent treatment strategies are summarized. RESULTS: All patients had <50% carotid stenosis before carotid endarterectomy. One patient had intraoperative occlusion and dissection of the internal carotid artery, which was noted on intraoperative carotid duplex ultrasound. All patients underwent postoperative computed tomography or computed tomography perfusion scans with subsequent cerebral angiography and stent reconstruction within 11 hours of symptom onset. In all cases, carotid recanalization was successfully completed between 32 and 160 minutes from groin puncture. There were no procedural complications. Four patients had a tandem middle cerebral artery occlusion, 3 of whom underwent successful recanalization. CONCLUSION: Emergent endovascular evaluation in the setting of acute post–carotid endarterectomy thrombosis is a safe and timely treatment option, with the benefit of detecting and treating embolic intracranial lesions. Immediate angiography and intervention in this rare surgical complication show promising initial results.